Associação entre sarcopenia, obesidade sarcopênica e força muscular com variáveis relacionadas de qualidade de vida em idosas - Silva Neto, Luiz Sinésio (2011)
Objective: To investigate the association between sarcopenia, sarcopenic obesity and muscle strength and variables related to quality of life in elderly women. Method: The sample consisted of 56 female volunteers who underwent body composition analysis (BMI and x-ray absorptiometry dual-energy DXA). Handgrip strength was measured using a Jamar dynamometer. We used the SF-36 health questionnaire to analyze quality of life. The data were analyzed with descriptive statistics and the Pearson correlation coefficient; SPSS 15.0 was used to perform the statistical analysis. Results: The mean age of the subjects was 64.92±5.74 years; of the 56 volunteers evaluated, 19.64% (n=11) were classified as sarcopenic obese and 45 (80.36%) were not. Thirteen volunteers (23.21%) were classified as sarcopenic while 43 (76.78%) were not. Although there were no statistically significant differences between the studied parameters and quality of life among those with sarcopenia or sarcopenic obesity, the values were lower in affected individuals. Interestingly, handgrip strength correlated positively and significantly with all of the SF-36 dimensions except VIT (p=0.08) and SM (p=0.25). Conclusions: Seeing that handgrip strength is a determining factor in quality of life aspects in this population, the screening and identification of small functional changes using simple clinical measures may facilitate early intervention and help prevent disability. In contrast, neither sarcopenia nor sarcopenic obesity were found to be associated with quality of life.